Morphological Characterization of Isolates of Phomopsis vexans of Bangladesh - Islam, MM; Asaduzzaman, M; Hoque, ME; Meah, MB (Journal of Science Foundation, 2013)
Forty four isolates of Phomopsis vexans from different eggplant cultivars collected from core eggplant growing regions of Bangladesh which were characterized using mycological characteristics. Variation exists among the isolates of Phomopsis vexans of Bangladesh covering two types of farm having two ecosystems and the isolates were grouped into five distinct groups based on their cultural properties. The highest sized ? conidia were observed in group -1 and the lowest size in-group -2. The highest sized ? conidia were recorded in group -5 and the lowest in-group 2. The highest pycnidial size noted in-group -3 and the smallest sized pycnidia were recorded in group 1. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14635 J. Sci. Foundation, 8(1&2): 123-130, June-December 2010